PERKEMBANGAN INTERPRETASI “KE BELAKANG TABIR” (IBR. 6:19, 20) DI DALAM GEREJA MASEHI ADVENT HARI KETUJUH - Franklin Hutabarat (Fakultas Filsafat Universitas Advent Indonesia, 2014)
In the study of the heavenly sanctuary and Christ's ministry in it, theinterpretation of the phrase “within the veil” (Heb. 6:19-20) and its implicationshave become one of crucial contentious theological issues among interpreterswithin the Seventh-day Adventist (SDA) Church. In the 160 year history of theSDA Church, there have been crucial theological debates on the interpretation ofthe phrase. Many SDA Church administrators, ministers, and scholars haveagreed and disagreed with one another on the interpretation of the phrase and itsimplications. The debate over the interpretation of the phrase